(untitled) (Globalization and Business, 2018)
Economic development looks at a wider range than GDP per capita. Economic development is concerned with how people are actually affected. It looks at their actual living standards and social conditions. Measures of Economic development will look at: Real income per head – GDP per capita; Levels of literacy and education standards; Levels of healthcare (e.g. number of doctors per 1,000 population); Quality and availability of housing; Levels of environmental standards; Levels of infrastructure (transport, communication); Levels of corruption; Educational standards & labor productivity; Labor mobility; Flow of foreign aid & investment; Level of savings & investment etc.